プリンス・オラフ エアンガン チイキ ニ オケル ショクセイ ヨホウ - 小林, 圭介; コバヤシ, ケイスケ; KOBAYASHI, Keisuke (国立極地研究所, 1974)
P(論文) From December 30, 1973 to February 4, 1974, phytosociological investigations were made on outcrops in the following four areas along the Prince Olav Coast: Cape Hinode, East and West Ongul Islands, Ongulkarven Island and Langhovde. On the basis of physiognomy, the communities were classified as follows: Moss community, Moss-Lichen community, Lichen community, Alga-Lichen community and Alga community. The distribution of plant communites was also surveyed on East and West Ongul Islands. The communities were distributed mostly on the west side of both East and West Ongul Islands, and only a few were found on the east side. According to these facts, it is found that there is a line dividing the Ongul Islands into two parts which are different in development of the vegetation. departmental bulletin paper